Comparative Study between Obstructive and Non-Obstructive Renal Anomalies Among a Group of Iraqi Children (Iraqi Journal of Medical Sciences, 2021)
Background: Congenital anomalies of the kidney and the urinary tract (CAKUTs) are relatively common birth defects and account for 40-50% of the etiology of chronic kidney disease (CKD) in children worldwide.Objective: To study the types of renal anomalies (RA) and to compare between obstructive and non-obstructive RA in relation to demographic data and complications.Methods: A descriptive study conducted in Al Imamein Kadhimein Medical City spanning the period from the 1st of February 2020, to the 30th of July 2020. Data collected were: type of renal anomaly, age of diagnosis, family history of RA, consanguinity, clinical presentation and associated complications.Results: In this study, 160 patients were included. Males were more affected than females 1.54:1. Most of the patients, 78 (48.8%), diagnosed were ?5 age group. Most of the patients, 124 (77.5%), had negative family history, vesicoureteral reflux (VUR) was the commonest anomaly detected in 67 patients (41.9%), followed by renal agenesis in 24 patients (15.0%). Urinary symptoms were most common presentation in 93 patients (58.1%). A higher complication was urinary tract infection (UTI) (62.5%). Comparison between obstructive and non-obstructive RA, reveled age of diagnosis and hydronephrosis has significant difference. While family history, UTI, failure to thrive, and chronic kidney disease stages was not significant.Conclusion: The commonest renal anomaly was VUR, the most prominent complication was UTI. Gender, age of diagnosis and hydronephrosis has significant difference between obstructive and non-obstructive RA.Keywords: Renal, anomalies, childrenCitation: Ali SH, Kadhim SA, Al-Obaidy QMAH. Comparative study between obstructive and non-obstructive renal anomalies among a Group of Iraqi children. Iraqi JMS. 2021; 19(2): 194-201. doi: 10.22578/IJMS.19.2.9
Keywords: Renal; anomalies; children